Договірна політика Польщі і Литви в рамках економічних відносин - Галевска, І.; Galewska, I. (Східноєвропейський національний університет імені Лесі Українки, 2013)
The aim is to analyze the articles of treaty policy in the business relationship Polish and Lithuanian. In this article the author has examined the legal status of economic relations from 1991 to 2011.
Contracting policy of Poland and Lithuania within the framework of economic relations
І.Галевска (Iwona Galewska), аспіранткa Опольського Університету (Uniwersytet Opolski), (Польща, м.Ополе) Науковий керівник: проф., докт. габ. Інституту політології Департаменту соціальних наук Вармінсько-Мазурського університету О.Васюта (О. Wasyuti) (Польща м. Ольштин)
Keywords: treaty policy; Poland; Lithuania; economic relations